Cerebrospinal Fluid Cytokines and Neurodegeneration‐Associated Proteins in Parkinson's Disease. Issue 6 (4th March 2020) - Wijeyekoon, Ruwani S.; Moore, Sarah F.; Farrell, Krista; Breen, David P.; Barker, Roger A.; Williams‐Gray, Caroline H.
Abstract: Introduction: Immune markers are altered in Parkinson's disease (PD), but relationships between cerebrospinal fluid (CSF) and plasma cytokines and associations with neurodegeneration‐associated proteins remain unclear. Methods: CSF and plasma samples and demographic/clinical measures were obtained from 35 PD patients. CSF samples were analyzed for cytokines (together with plasma) and for α‐synuclein, amyloid β(1‐42) peptide, total tau, and phospho(Thr231)‐tau. Results: There were no CSF–plasma cytokine correlations. Interleukin (IL)‐8 was higher and interferon‐γ, IL‐10, and tumor necrosis factor–α were lower in CSF versus plasma. In CSF, total tau correlated positively with IL‐8 and IL‐1β, whereas α‐synuclein correlated positively with amyloid β(1‐42) and negatively with semantic fluency (a known marker of PD dementia risk). Discussion: CSF and peripheral cytokine profiles in PD are not closely related. Associations between CSF IL‐8 and IL‐1β and tau suggest that CSF inflammatory changes may relate to tau pathology within PD. CSF α‐synuclein/amyloid β may reflect the risk of developing PD dementia. © 2020 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.